2015
DOI: 10.1155/2015/439345
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style: School Perspective in Cameroon

Abstract: This paper examines leadership styles of secondary school principals in Cameroon, in terms of transformational, transactional, and laissez-faire leadership styles. This paper discusses the leadership styles in Cameroon and puts forward ideas for continuous improvement. A qualitative approach, using a semistructured interview, was adopted. It was conducted on ten principals, ten teachers, and ten students. Majority of respondents from schools described their principals as transformational leaders. Doubts are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This exemplified in the process followed by the Sahaba of the Holy Prophet (SAW) in establishing a successor after his passing, which involved seeking advice from the public and obtaining collective consent for endorsement. The subsequent Caliphs, including Abu Bakr Siddiq (RA) and 'Umar ibn al-Khattab, were appointed and confirmed through similar processes 38 . Islam promotes individual autonomy of thought, which effectively demonstrated by the Four Khalifs of Islam as an integral component of leadership.…”
mentioning
confidence: 84%
“…This exemplified in the process followed by the Sahaba of the Holy Prophet (SAW) in establishing a successor after his passing, which involved seeking advice from the public and obtaining collective consent for endorsement. The subsequent Caliphs, including Abu Bakr Siddiq (RA) and 'Umar ibn al-Khattab, were appointed and confirmed through similar processes 38 . Islam promotes individual autonomy of thought, which effectively demonstrated by the Four Khalifs of Islam as an integral component of leadership.…”
mentioning
confidence: 84%
“…Because examining the professional activity of school principals helps to structure, develop, and identify key competencies to exercise this profession, we deemed it of relevance to apply these research findings to the context in Cameroon. While studies on principals' professional practices in francophone and anglophone secondary education are rare in this country (Besong Besong, 2013Lyonga, 2019;Wirba, 2015), they do touch upon their professional activities and standards under different angles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besong Besong (2013), Lyonga (2019) and Wirba (2015) studied school management competencies from another perspective, in the southwest region of Cameroon. Besong Besong (2013), who examined the level of effectiveness of both private and public-school principals in Cameroon (more specifically in the city of Maroua), found that the principals' practices in these two sectors differed significantly regarding shared leadership, staff motivation, administrative management, and financial resources management.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to mention that, School leaders start out as teachers and advance to the position of school leader at the end of their teaching career. Wirba (2015) attest that "the speed at which classroom teachers are turned into school principals indicate the lack of emphasis on leadership training for current principals in schools in Cameroon, meaning the average school principal in Cameroon context has no special qualities and experiences over the teaching staff. This seniority-based transition of teacher to school leadership (recruitment policies and procedures) therefor overlook knowledge and experience of education management and leadership with the assumptions that the new principals has already got relevant experiences for his new role and will have more skills and experiences on the job training.…”
Section: Introductionmentioning
confidence: 99%